Contribution of electrolyte in parametric optimization of perfluorooctanoic acid during electro-oxidation: Active chlorinated and sulfonated by-products formation and distribution. (January 2023) - Qiao, Qicheng; Singh, Seema; Patidar, Ritesh; Wang, Lizhang; Li, Ya; Shi, Jian; Chandra Srivastava, Vimal; Lo, Shang-Lien
Abstract: The present study investigated the roles of peroxydisulfate (PDS) radicals and sulfate radicals (SO4 − ) that formed from sulfate (SO4 2− ) during electrochemical oxidation of perfluorooctanoic acid (PFOA). The effect of operating parameters such as different types of electrolytes (NaCl, NaClO4, and Na2 SO4 ), initial pH, current density, dose of electrolyte, and initial concentration of PFOA using electrochemical oxidation for perfluorooctanoic acid (PFOA) decomposition study was investigated. A difference in the removal efficiency with different electrolytes (i.e., Cl −, ClO4 −, and SO4 2− ) illustrated an increasing effect of electrooxidation of PFOA in the order of ClO4 −  < Cl −  < SO4 2−, which suggested that OH induced oxidation and direct e − transfer reaction continued to play a crucial role in oxidation of PFOA. At the optimum treatment condition of j = 225.2 Am −2, Na2 SO4 concentration = 1.5 gL −1, [PFOA]o  = 50 mgL −1 and initial pH = 3.8 maximum PFOA removal of 92% and TOC removal of 80% was investigated at 240 min. The formation of three shorter-chain perfluorocarboxylates (i.e., perfluoroheptanoic acid (PFHpA), perfluorohexanoic acid (PFHxA), and perfluoropentanoic acid (PFPeA) and formate (HCOO − ) ions were detected as by-products of PFOA electro-oxidation, showing that the C–C bond first broken in C7 F15 and then mineralized into CO2, and fluoride ion (F − ). The fluorine recovery as F − ions and the organic fluorine as the shorter-chain by-products were also obtained. The degradation kinetic has also been studied using the nth-order kinetic model. Graphical abstract: Image 1 Highlights: Perfluorooctanoic acid (PFOA) decomposition using Ti/SnO2 –Sb/PbO2 anodes. Formation and distribution of electrolyte-derived reactive oxygen species. Effect of operating parameters on PFOA mineralization. Qualitative and quantitative analysis of PFOA decomposition. Detection of oxyanion species i.e., ClO2 −, ClO3 −, ClO4 – HSO5 −, and S2 O8 2− .